O Curso Aristotélico Jesuíta Conimbricense - Mário Santiago de Carvalho (Classica Digitalia: Portugaliae Monumenta Neolatina, 2018)
Between 1592 and 1606, four jesuit professors from the College of Coimbra published a course of Aristotelian Philosophy, known by the title Commentarii Collegii Conimbricensis Societatis Jesu. Given its intrinsic value, he eventually knew a global influence: from the Atlantic to the Urals, the Far East and Latin America. Also some eminent philosophers (e.g. Descartes or Peirce) were readers of the work of Coimbra but, due to the numerous editions that the work met abroad, its overwhelming presence in the european university libraries, has determined the study of philosophy by thousands of students. Written in an accessible language, this monograph aims to give an updated, systematic and rigorous perspective of the main themes addressed in the work Coimbra - logic, physics, psychology, ethics and metaphysics - for the first time presented as «an exposition of philosophical science in a systematic, deductive and disputational form».